2011
DOI: 10.1007/s00066-011-2222-x
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary small cell carcinoma: An indication for prophylactic cranial irradiation?

Abstract: The incidence of brain metastases was relatively low (13%). More studies are necessary, before routinely offering PCI to patients with EPSCC. Best survival outcomes in LS were achieved with multimodality treatment including CT and RT. Prognosis was poor in patients with ES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
(61 reference statements)
2
16
0
Order By: Relevance
“…In addition, Eckert et al [1] showed in their retrospective analysis of 51 patients that the incidence of CM in EPSCC was lower than that of SCLC (21.5%, while the incidences of primary CM and secondary CM were 10% and 11.8%, respectively) vs. 40-80%.These results are in concordance of our results (incidence of secondary CM from SCCB =17%) and with the results of the English-language literature [2,7,14]. Due to the low incidence of CM, the authors concluded that PCI should not be recommended in general [1,9].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…In addition, Eckert et al [1] showed in their retrospective analysis of 51 patients that the incidence of CM in EPSCC was lower than that of SCLC (21.5%, while the incidences of primary CM and secondary CM were 10% and 11.8%, respectively) vs. 40-80%.These results are in concordance of our results (incidence of secondary CM from SCCB =17%) and with the results of the English-language literature [2,7,14]. Due to the low incidence of CM, the authors concluded that PCI should not be recommended in general [1,9].…”
supporting
confidence: 92%
“…I also agree that the most effective chemotherapy regimens are those of neuroendocrine type, in analogy with SCLC [2,3,4,5,6,7,11,14]. EPSCC is very chemosensitive; the objective response rates approach 100%, and EPSCC have a high metastatic potential [2,4,5,7,14]. Consequently, neoadjuvant chemotherapy may play a very important role, as has been demonstrated for SCCB [11,12].…”
mentioning
confidence: 76%
“…Due to these results, PCI became a mainstay in the treatment of SCLC. However, as CM rates in EPSCC were significantly lower, routine use of PCI was not recommended in EPSCC [14,28]. Walenkamp et al [28] discussed it for patients with head and neck malignancies due to CM rates of up to 44% in this patient group [3].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lower incidence of brain metastases in EPSCC [9], PCI is not routinely recommended in these patients [14]. However, it is discussed in patients with head and neck malignancies [28], due to a 44% rate of cerebral metastases at 5 years for this location [3].…”
Section: Implications For the Use Of Prophylactic Cranial Irradiationmentioning
confidence: 99%
“…Eight studies (n = 14) were included in the current analysis ( Figure 6) [16][17][18][19][20][21][22][23] . Studies that did not provide separate information for patients with LNEPSCC [29][30][31][32][33][34][35][36][37][38][39][40][41] , and the treatment given or follow up were not included in the current review [42][43][44][45][46][47][48][49][50] . A total of 17 patients including the three index cases (mean ± SD, 59.5 ± 10.8 years; 81.8% males) with LNEPSCC were included in the current analysis (Table 1).…”
Section: Systematic Reviewmentioning
confidence: 99%